Comparative Analysis of Key Labour Market Indicators in the Creative Industries Across Russia’s Northwestern Federal Okrug - Kropinova , Elena G.; Mondych , Andrey S. (Economy of Regions, 2026)
In April 2025, the Russian Ministry of Economic Development officially classified certain activities as creative industries, underscoring the need to update data on their contributions to regional economies and employment. This study aims to assess the current state of the labour market in the creative industries across the regions of Russia’s Northwestern Federal Okrug. While previous approaches covered more industries and relied on labour force surveys rather than organization-level data, the proposed methodology uses a resource-based approach to human capital assessment, combining an industry-focused analysis of employment indicators in creative industry organizations with a labour market analysis, including hh-index indicators. The results confirm that the labour market in creative industries is highly competitive, with a decline in vacancies compared to 2024. In most of the given regions, the share of creative industry employees is below the national average, except in Saint Petersburg and Pskov Oblast. Using a range of indicators, the study ranks the regions according to a creative human capital index for the labour market and identifies the most promising regions for creative industry development: Kaliningrad, Murmansk, Leningrad, Pskov, and Novgorod. To stimulate growth in this sector, the authors suggest establishing preferential conditions for creative industries in existing economic zones. The study also highlights the need to refine the Ministry-approved list of economic activities classified as creative industries.